2019
DOI: 10.1002/pmrj.12047
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Comparison of Five‐Year Health Outcomes Following Upper Limb Amputation and Serious Upper Limb Injury in the Iraq and Afghanistan Conflicts

Abstract: Background: Limited population-based research has described long-term health outcomes following combat-related upper limb amputation. Objective: To compare health outcomes following upper limb amputation with outcomes following serious upper limb injury during the first 5 years postinjury. Design: Retrospective cohort. Setting: Departments of Defense (DoD) and Veterans Affairs (VA) inpatient and outpatient health care facilities. Participants: Three-hundred eighteen U.S. Service Members. Methods: Patients sust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Previous research has shown that active duty military personnel who sustain extremity injuries while in service are at elevated risk for serious physical and psychological health issues that could affect their long-term functioning and quality of life, [6][7][8][9][10][11][12][13][14][15][16] yet no prior studies have examined longer-term mortality in this population. This study addressed this knowledge gap by examining all-cause and cause-specific mortality rates among service members who sustained serious extremity injuries while in service.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has shown that active duty military personnel who sustain extremity injuries while in service are at elevated risk for serious physical and psychological health issues that could affect their long-term functioning and quality of life, [6][7][8][9][10][11][12][13][14][15][16] yet no prior studies have examined longer-term mortality in this population. This study addressed this knowledge gap by examining all-cause and cause-specific mortality rates among service members who sustained serious extremity injuries while in service.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous physical comorbidities are associated with extremity injuries, including weight gain, lingering pain, joint disorders, and cardiovascular disease, as well as associated risk factors, such as metabolic syndrome. [6][7][8][9][10][11][12][13][14][15][16] Further, evidence suggests that rates of psychological disorders, such as posttraumatic stress disorder and depression, are high following extremity injury, including injuries that required amputations. [17][18][19] Although morbidity has been well characterized among individuals with severe extremity injuries, [6][7][8][9][10][12][13][14][15][16][17][18] mortality has been understudied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying and understanding the influencing factors are very important to the early prevention and nursing care of ASD. Previous studies (Melcer et al, 2019 ; Mona et al, 2019 ) have pointed out that the patient’s trauma history, complications, and degree of trauma can damage important functions of the body, loss of self‐care, self‐reliance, and social function, resulting in more serious ASD. Fear, anxiety and depression during injury can cause brain atrophy (Qiong et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have routinely captured health outcomes or examined the diverse nature of pain experiences in the 24 months following combat-related injury. 28 Uniquely, this study measured a range of pain-related symptoms from the time of initial injury through recovery. While not statistically significant, individuals receiving early RA reported lower mean neuropathic pain quality and intensity scores as well as higher mean TOPS domain score, such as greater satisfaction with outcomes, compared with those who did not receive early RA.…”
Section: Original Articlementioning
confidence: 99%